RISK ANALYSIS OF INSAN UNIVERSITY SYSTEM USING ISO 27001 - Raniyah Ayu Lestari; Dedy Syamsuar (Jurnal TAM (Technology Acceptance Model), 2020)
This study aims to apply the governance of Information and Communication Technology (ICT) at Bina Insani University. Governance itself has become a necessity and a demand in the application of ICT management. This study uses the ISO 27001 standard in measuring and assessing information security risks. Data collection is done by using the method of observation and interviews. The stages of research carried out in a row are (1) Identification of assets, (2) identification of security threats and vulnerabilities, (3) assessing CIA risk (Confidentiality integrity availability), (4) BIA business impact assessment (5) Resulting risk value is accepted or carried out management until risk evaluation Risk evaluation results show that there are still many activities that must be improved such as information disclosure and malware spread and implemented to improve the security of assets at the university of human development.